Diffusion-weighted and perfusion MRI demonstrates parenchymal changes in complex partial status epilepticus - Szabo, Kristina; Poepel, Annkathrin; Pohlmann-Eden, Bernd; Hirsch, Jochen; Back, Tobias; Sedlaczek, Oliver; Hennerici, Michael G.; Gass, Achim (Brain, 2005)
Diffusion-weighted MRI (DWI) and perfusion MRI (PI) have been mainly applied in acute stroke, but may provide information in the peri-ictal phase in epilepsy patients. Both transient reductions of brain water diffusion, namely a low apparent diffusion coefficient (ADC), and signs of hyperperfusion have been reported in experimental and human epilepsy case studies. We studied 10 patients with complex partial status epilepticus (CPSE) with serial MRI including DWI and PI. All patients showed regional hyperintensity on DWI, and a reduction of the ADC in (i) the hippocampal formation and the pulvinar region of the thalamus (six out of 10 patients), (ii) the pulvinar and cortical regions (two out of 10), (iii) the hippocampal formation only (one out of 10), and (iv) the hippocampal formation, the pulvinar and the cortex (one out of 10). In all patients a close spatial correlation of focal hyperperfusion with areas of ADC/DWI change was present. In two patients hyperperfusion was confirmed in additional SPECT (single photon emission computed tomography) studies. All patients received follow-up MRI examinations showing partial or complete resolution of diffusion and perfusion abnormalities depending on the length of the follow-up interval. The clinical course, EEG and SPECT results all indicate that MRI detected changes related to prolonged epileptic activity. Combined PI and DWI can visualize haemodynamic and tissue changes after CPSE in the hippocampus, thalamus and affected cortical regions.